Design and development of microcontroller based ECG simulator - Uzoshi, Khandaker Raska; Arsalan, Adnan; Datta, Robi Shankar; Paul, Andre Dominic (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.